DK1 Induces Apoptosis via Mitochondria-Dependent Signaling Pathway in Human Colon Carcinoma Cell Lines In Vitro - Yazmin, Hussin; Muhammad Nazirul Mubin, Aziz; Nurul Fattin, Che Rahim; Swee, Keong Yeap; Nurul Elyani, Mohamad; Mas Jaffri, Masarudin; Noraini, Nordin; Nik Mohd Afizan, Nik Abd Rahman; Chean, Yeah Yong; Akhtar, Muhammad Nadeem; Siti Noor Hajar, Zamrus; Noorjahan Banu, Alitheen (MDPI - Open Access Publishing, 2018)
Extensive research has been done in the search for innovative treatments against colon adenocarcinomas; however, the incidence rate of patients remains a major cause of cancer-related deaths in Malaysia. Natural bioactive compounds such as curcumin have been substantially studied as an alternative to anticancer drug therapies and have been surmised as a potent agent but, nevertheless, remain deficient due to its poor cellular uptake. Therefore, efforts now have shifted toward mimicking curcumin to synthesize novel compounds sharing similar effects. A synthetic analog, (Z)-3-hydroxy-1-(2-hydroxyphenyl)-3-phenylprop-2-ene-1-one (DK1), was recently synthesized and reported to confer improved bioavailability and selectivity toward human breast cancer cells. This study, therefore, aims to assess the anticancer mechanism of DK1 in relation to the induction of in vitro cell death in selected human colon cancer cell lines. Using the3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide(MTT) assay, the cytotoxicity of DK1 towards HT29 and SW620 cell lines were investigated. Acridine orange/propidium iodide (AO/PI) dual-staining assay and flow cytometry analyses (cell cycle analysis, Annexin/V-FITC and JC-1 assays) were incorporated to determine the mode of cell death. To further determine the mechanism of cell death, quantitative real-time polymerase chain reaction (qRT-PCR) and proteome profiling were conducted. Results from this study suggest that DK1 induced changes in cell morphology, leading to a decrease in cell viability and subsequent induction of apoptosis. DK1 treatment inhibited cell viability and proliferation 48 h post treatment with IC50 values of 7.5 ± 1.6 µM for HT29 cells and 14.5 ± 4.3 µM for SW620 cells, causing cell cycle arrest with increased accumulation of cell populations at the sub-G0/G1phaseof 74% and 23%, respectively. Flow cytometry analyses showed that DK1 treatment in cancer cells induced apoptosis, as indicated by DNA fragmentation and depolarization of the mitochondrial membrane. qRT-PCR results show significant upregulation in the expression of caspase-9 in both HT29 and SW620 cell lines, further supporting that cell death induction by DK1 is via an intrinsic pathway. These outcomes, therefore, demonstrate DK1 as a potential anticancer agent for colon adenocarcinoma due to its anti-apoptotic attributes